PENGOLAHAN PANGAN DENGAN CARA FERMENTASI - Alhanannasir, Alhanannasir; Sebayang, Nico Syahputra; Parameswara, Prasetyo; Berlian, Alviona; Prisiantika, Intan; Saputra, Ilham; Ayu, Fidia; Idealistuti, Idealistuti; Murtado, Asep Dodo (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Fermentation is a food processing technique that utilizes microorganisms to extend shelf life, enhance nutritional value, and produce safer products with unique flavor characteristics. The fermentation process can occur naturally or with the addition of a starter, depending on the type of product being produced. This technique has been widely applied in traditional food processing across various regions, using raw materials such as soybeans, vegetables, tubers, milk, and meat. Fermented products serve not only as food sources but also as functional foods that benefit health, including as sources of antioxidants and probiotics. This study examines the advantages of fermentation as a preservation method and explains the biochemical processes that occur during fermentation, including the role of lactic acid bacteria (LAB) in improving the quality of the final product.